PENGARUH EKSPOR DAN IMPOR INDONESIA TERHADAP BISNIS INTERNASIONAL (Jurnal Manajemen Kreatif dan Inovasi, 2023)
International trade is trade carried out between countries by carrying out export and import activities. International trade is the international exchange of goods and services across international borders. This is usually accompanied by the added risk of changes in exchange rates. The purpose of this analysis is to determine the influence of international trade on Indonesia, where the author uses descriptive research and collects information and analyzes data using secondary data. From this analysis, it can be seen the impact of international trade and its impact on Indonesia